An advanced technology for structural crashworthiness analysis of a ship colliding with an ice-ridge: Numerical modelling and experiments - Ince, Serdar Turgut; Kumar, Ankush; Park, Dae Kyeom; Paik, Jeom Kee (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
The structural engineering problem associated with a ship colliding with an ice-ridge involves highly nonlinear mechanisms including buckling, collapse, crushing, plasticity and fracture together with environmental and operational factors, such as the loading speed (strain rate), temperature and salinity. The objective of this paper is to develop an advanced technology for numerical computations of structural crashworthiness in the event of a ship colliding with an ice-ridge. The nonlinear finite element method is used for modelling the problem, in which the ship structures are modelled by plate-shell finite elements and the ice-ridge structures are modelled by solid elements together with the KOSORI ice material models. Two sets of experiments are performed to validate the numerical computations. In the first set of experiments, ice is dropped on a steel plate from a height of 2 m, and in the second, a steel solid (rigid) body is dropped on a steel plate under the same conditions. The results of the two experiments are compared to determine the differences between the ice responses and solid (rigid) body responses on the steel plate. It is concluded that the developed technology is very useful for computing the structural crashworthiness of a ship when colliding with an ice-ridge. Details of the test results are documented. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Structural crashworthiness; Collisions between ships and ice-ridges; Impact engineering; Fracture; Plasticity; Engineering; Mechanics